Mechanical Valve Replacement: Early Results - Habib Cakir; Hasan Uncu; Funda Tor; Gurdeniz Yildiz; Ali Haci Ucak; Ibrahim Ozsoyler (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2012)
Aim: Valve diseases in developing countries like Turkey which often occur as a complication of rheumatic fever are a serious disease. Surgical treatment of valve diseases should be done before irreversible damage to the myocardium occurred. In this study, we aimed to present the early results of mechanical valve replacement operations. Method: A hundred patients with mechanical valve replacement surgery were retrospectively evaluated in Seyhan Application Center attached to our clinic between July 2007 and August 2011. Results: Fifty patients were male and 50 were women. The mean age of patients was 47.88 (18-78). Isolated aortic valve replacement (AVR) was performed to 23 patients, isolated mitral valve replacement (MVR) was 32, double valve replacement (AVR + MVR) was 12, MVR + aortic valve valvuloplasty was 1, AVR + mitral kommissurotomi was 1, AVR + coronary artery bypass graft surgery (CABG) was 17, MVR + CABG was 8, MVR + atrial septal defect closure was 2 and Bentall procedure.was 4 patients. In addition, ablation procedure was performed to 5 patients intraoperatively because of preoperative atrial fibrillation. Two patients (2 %) died in early postoperative period. Conclusion: Mechanical prosthetic valves are used for surgical treatment of valve disease with low mortality and morbidity in a large group of patients like women that not to think to get pregnant, non advanced age group and patients have less risky for anticoagulation drug in our clinic. [Cukurova Med J 2012; 37(1.000): 49-54]